Effect of an orally formulated processed black cumin, from Iranian traditional medicine pharmacopoeia, in relieving symptoms of knee osteoarthritis: A prospective, randomized, double‐blind and placebo‐controlled clinical trial. (5th April 2017) - Salimzadeh, Ahmad; Ghourchian, Anahita; Choopani, Rasool; Hajimehdipoor, Homa; Kamalinejad, Mohammad; Abolhasani, Maryam
Abstract: Aim: Osteoarthritis is a global health problem, especially for the elderly. A good replacement for non‐surgical treatments is the use of traditional medicines. We selected a revere plant (Nigella sativa L.), a widely utilized medicinal herb for the treatment of inflammatory conditions, from the Iranian traditional medicine (ITM) pharmacopoeia with proven anti‐inflammatory and analgesic actions. Methods: We performed a prospective, randomized, double‐blind, and placebo‐controlled clinical trial, in order to investigate whether the herb is useful in alleviating the symptoms of knee osteoarthritis. American College of Rheumatology clinical criteria were the basis of diagnosis, while the Knee injury and Osteoarthritis Outcome Score (KOOS) questionnaire was considered as the main outcome measure. One hundred and ten eligible patients were assigned to receive a placebo or an active intervention (2 g/day of processed N. sativa seed powder in divided doses). Acetaminophen tablets were the rescue medicine. Finally, 40 patients in the placebo group and 37 patients in the active group completed the trial and were included in the statistical analysis. Results: Both cohorts demonstrated statistically significant within‐group differences ( P < 0.05) in some subscales that were more prominent in the active group without any considerable adverse effects. Nevertheless, KOOS score results and the mean number of acetaminophen tablets used by patients showed no statistically significant between‐group differences. Conclusions: It can be concluded that future programmed studies with larger sample sizes, longer follow‐up periods, and other forms of N. sativa seeds as an active intervention is necessary to evaluate its efficacy in relieving the symptoms of knee osteoarthritis.